Tuning the d-band center of NiC2O4 with Nb2O5 to optimize the Volmer step for hydrazine oxidation-assisted hydrogen production. Issue 14 (29th June 2022) - Chen, Xiao Hui; Fu, Hong Chuan; Wu, Li Li; Li, Xiao Lin; Yang, Bo; Li, Ting; Gu, Fei; Lei, Jing Lei; Li, Nian Bing; Luo, Hong Qun
Abstract : Nb2 O5 can adjust the electronic structure of SNiC2 O4 and improve the catalytic activity. Replacing the OER with the HzOR for hydrogen production can save 80% of energy consumption. Abstract : Replacing the thermodynamically unfavorable oxygen evolution reaction (OER) with the low theoretical potential (−0.33 V) and safe by-product (N2 /H2 O) hydrazine oxidation reaction (HzOR) is an energy-saving way for hydrogen production. Nevertheless, the complexity of bifunctionality increases the difficulty of catalyst design. In this work, a hybrid of NiC2 O4 and Nb2 O5 is synthesized on nickel foam via a two-step low temperature reaction using Ni3 S2 as a sacrificial template, named SNiC2 O4 –Nb2 O5 /NF. The experimental and theoretical calculation results illustrate that electrons are transferred from Ni to Nb, thus regulating the electronic structure of Ni. In the hybrid, Nb2 O5 can effectively adsorb and split H2 O, as well as downshift the d-band center of SNiC2 O4, thereby optimizing the Volmer step. SNiC2 O4 –Nb2 O5 /NF achieves the properties for the hydrogen evolution reaction (HER: η 20 = 155 mV) and the oxygen evolution reaction (OER: η 20 = 293 mV). The addition of hydrazine to an alkaline electrolyte can decrease the cell voltage by 1.41 V when the current density is 20 mA cm −2, and achieve a high-speed hydrogen yield driven by an AA battery. This work puts forward an idea for the rational design of environmentally friendly and effective hybrid catalysts.